Y-balance test in female gymnasts - Milcic, L.; Milenkovic, E.; Radaš, J. (Proceedings of the 12th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2024)
The aim of this study was to examine the differences in dynamic balance between the legs and potential asymmetry in rhythmic gymnasts. The sample consisted of six rhythmic gymnasts competing at the senior level A category and members of the Croatian National Team. Dynamic balance was assessed using the "Y Balance" test. Each gymnast performed the test in the anterior, posteromedial, and posterolateral directions, following a practice attempt. Data analysis was conducted using Statistica 14. Differences in Y Balance test performance between the dominant and non-dominant leg were evaluated using the T-test for dependent samples, as well as the Wilcoxon Matched Pairs Test for variables that did not follow a normal distribution. The results revealed a statistically significant difference in the posteromedial reach distance between the dominant and non-dominant legs, indicated by variables RRDPMD and RRDPMND (p=0.021). This disparity was evident in both absolute and relative terms, with t he dominant leg demonstrating a greater reach distance. These findings suggest that the gymnasts exhibit a preference for one leg over the other, potentially affecting performance and increasing the risk of injury. Monitoring these asymmetries is crucial for developing targeted training interventions to enhance balance and functional performance.